Konsep Pemikiran Filsafat Aristoteles dan Charles Sanders Peirce - Haq, Izul Haq Lidinilah; Izul, Izul Haq Lidinilah; Muhammad Cholil Alwi (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2024)
Aristotle was a Greek Classical philosopher who lived in the 4th century BC. He is a central figure in the world of philosophy, through his thought patterns and works he created a paradigm in the science of philosophy, even in the course of philosophy until the modern era it is still studied and relevant. For example, in Metaphysics, he says that the soul and body are a unified whole, so if the body dies the soul will disappear. This opinion has had a big influence in the world of Islamic philosophy, that is, its influence is very broad. It is also important, as a comparison, to understand modern philosophers, Charles Sanders Peirce was a 19th century philosopher, he made contributions to the world of Modern philosophy, especially in his thoughts on Pragmatism, that an action must be in accordance with the purpose for which it is served. By these two philosophical thinkers, this article is here to provide an analysis of both. This research uses a qualitative approach with a type of literature study, namely reviewing books or writings related to the research carried out. The results of this research show that Aristotle's thinking is in the form of: Logic, Theoretical Philosophy, Practical Philosophy and finally Philosophy. As for Charles Sanders Peirce, his thoughts are in the form of: Semiotics and Semiotics   Keyword: Philosophical Thought, Aristotle, Charles Sanders Peirce